EXPLORING HOW LIVE STREAMING SHAPES MALE CONSUMERS’ PERCEPTIONS OF RATINGS AND REVIEWS - Eugenius Besli; Valentin R. G. Bella Adur; Yesita M. V. Mada Hekopung (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
This study aims to understand how consumer reviews, store ratings, and live streaming affect online shopping decisions among male consumers. It also looks into how live streaming can mediate the connection between reviews, ratings, and purchasing choices. We chose a purposive sampling method, focusing on male consumers who are often overlooked in similar research. Data was gathered online through questionnaires filled out by 170 students from three universities in Sikka Regency. To analyze relationships, we used multiple linear regression, and the Sobel Test helped us examine the mediation effects. The results are encouraging, showing that consumer reviews, store ratings, and live streaming all positively influence male consumers' online buying decisions. Interestingly, live streaming serves as a mediator between store ratings and purchase choices, but it doesn't play the same role between reviews and decisions. Overall, this research offers valuable insights into male consumer behavior in the world of e-commerce.